Respuesta :

Answer:

-12x + 12 = 32............................. the equation

Step-by-step explanation:

to determine the equation in this 12(1-x) = 36 expression is quite simple, you only need to open the bracket .

solution

12(1-x) = 36

12 - 12x = 32

-12x + 12 = 32............................. the equation

we  can further evaluate for the value of x  

-12x = 32 - 12

-12x = 20

divide both sides by the coefficient of x which is -12

-12x = 20

-12x/-12 = 20/-12

x =  -1.67

Answer:

-12x + 12 = 33
ACCESS MORE